Efeitos da troca plasmática terapêutica sobre os parâmetros de coagulação de cães com leishmaniose visceral - Maia, Suellen Rodrigues (Universidade Estadual Paulista (Unesp), 2025)
As observed in human medicine, therapeutic plasma exchange (TPE) has also become the focus of veterinary research due to its potential role in the management of immune-mediated diseases. In this context, conditions characterized by an excessive production of antibodies and immune complexes in response to antigenic stimulation, which may trigger deleterious effects on the organism, are of particular interest. Among these, canine visceral leishmaniasis (CVL) stands out, not only due to its high incidence and zoonotic potential but also because of the diverse systemic immunological effects it induces in affected patients. Thus, TPE emerges as a promising therapeutic modality, capable of contributing significantly to the treatment of such conditions. However, understanding the inherent characteristics of this extracorporeal procedure is essential to ensure that its therapeutic benefits outweigh any potential adverse effects. Given the scarcity of studies on TPE in veterinary patients, this study aimed to describe the effects of centrifugation-based TPE in dogs with CVL receiving fresh frozen plasma (FFP) as part of the replacement fluid. Thirty-one dogs were selected and allocated into two groups: a clinical treatment group (CTG, n = 18) and a clinical treatment plus TPE group (TPEG, n = 13). Dogs in the TPEG underwent one TPE session per day for three consecutive days (D1, D2, and D3). Blood samples were collected from all animals, with additional pre- and post-procedure samples obtained from those undergoing TPE. Coagulation profile analyses included platelet count, activated partial thromboplastin time (aPTT), prothrombin time (PT), ionized calcium (iCa), and fibrinogen levels. Results showed that, although TPE induced a progressive decrease in platelet counts throughout the sessions, it did not lead to significant thrombocytopenia or critical alterations in aPTT and PT, with values remaining within the reference range for the species. Transient hypocalcemia observed after the first session was promptly corrected with continuous intravenous calcium gluconate supplementation, preventing recurrence in subsequent sessions. Clinical complications were minimal, restricted to a single case of transfusion reaction and another of symptomatic hypocalcemia, both successfully managed. A slight reduction in fibrinogen levels was observed, without clinical hemorrhagic repercussions. It can be concluded that centrifugation-based TPE is a safe and potentially beneficial adjunctive therapy for CVL, with manageable effects on hemostasis and clinical homeostasis in affected dogs.
Effects of therapeutic plasma exchange on coagulation parameters in dogs with visceral leishmaniasis
Não se aplica
Keywords: Aférese; Cão; Coagulopatia; Sangramento; Trombose